β-Aminopropionitrile-induced aortic aneurysm and dissection in mice - Sawada, Hisashi; Beckner, Zachary A.; Ito, Sohei; Daugherty, Alan; Lu, Hong S. (JVS-vascular science, 2022)
The mechanistic basis for the formation of aortic aneurysms and dissection needs to be elucidated to facilitate the development of effective medications. β-Aminopropionitrile administration in mice has been used frequently to study the pathologic features and mechanisms of aortic aneurysm and dissection. This mouse model mimics several facets of the pathology of human aortic aneurysms and dissection, although many variables exist in the experimental design and protocols that must be resolved to determine its application to the human disease. In the present brief review, we have introduced the development of this mouse model and provided insights into understanding its pathologic features.